Comparative Study on Durability Properties of Engineered Cementitious Composites with Polypropylene Fiber and Glass Fiber - Ranjith S. (Archives of Civil Engineering, 2017)
The durability characteristics of Engineered Cementitious Composites (ECC) with various fibers such as polypropylene and glass were investigated in view of developing composites with high resistance to cracking. ECC offer large potential for durable civil infrastructure due to their high tensile strain capacity and controlled micro-crack width. In this study, fibre volume fractions (0.5%, 1%, 1.5%, and 2%) of both polypropylene and glass fibers varied and durability measures such as a rapid chloride penetration test, sorptivity, water absorption, acid attack, and sulphate attack were measured. Increasing the fiber content up to 1.5% improved the durability properties of ECC. The test results indicate that the glass fiber-reinforced Engineered Cementitious Composites have better durability characteristics than polypropylene fiber-reinforced ECC.